Low vision: the patient's perspective - Karin van Dijk (Community Eye Health Journal, 2012)
For this issue on low vision, the Community Eye Health Journal contacted low vision practitioners in India, Tanzania, Nepal, and Peru to help gather the views of eighteen people attending their low vision clinics. The people varied in age from 14 to 81, and suffered from a range of vision problems including nystagmus, retinitis pigmentosa, diabetic retinopathy, and bilateral aphakia.